2022
DOI: 10.3389/fnut.2022.829857
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Magnesium Intake Modifies the Association Between Vitamin D and Systolic Blood Pressure: Results From NHANES 2007–2014

Abstract: IntroductionAlthough the association between blood pressure and vitamin D has been well studied, the effects of dietary magnesium intake on this relationship are still unclear. Thus, this study aimed to determine the effects of dietary magnesium intake on the association between vitamin D and blood pressure.MethodsThe present study analyzed data from the continuous the National Health and Nutrition Examination Survey (NHANES) 2007–2014. We included 8,799 participants aged 20 years or older. Multivariable linea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Considering the positive effect of serum vitamin D on muscle strength ( 20 ), low magnesium intake might link with grip strength via affecting the synthesis and transport of 1,25(OH)2D. Similar interactions between low magnesium intake and serum 25(OH)D level were observed on insulin resistance, hypertension, diabetes, and cardiovascular mortality ( 17 19 , 40 ), but not on cognitive performance ( 41 ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Considering the positive effect of serum vitamin D on muscle strength ( 20 ), low magnesium intake might link with grip strength via affecting the synthesis and transport of 1,25(OH)2D. Similar interactions between low magnesium intake and serum 25(OH)D level were observed on insulin resistance, hypertension, diabetes, and cardiovascular mortality ( 17 19 , 40 ), but not on cognitive performance ( 41 ).…”
Section: Discussionmentioning
confidence: 82%
“…In addition, studies found that magnesium could affect the synthesis and metabolism of vitamin D ( 14 ), and meanwhile vitamin D could influence the absorption of magnesium ( 15 , 16 ). Interactive effect between magnesium intake and serum vitamin D status was observed on hypertension, diabetes and cardiovascular mortality ( 17 19 ). Considering the effect of vitamin D on muscle strength ( 20 ), whether interaction between magnesium intake and vitamin D also existed on muscle strength is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that the association between magnesium status and grip strength persists in the subgroup of vitamin D sufficient individuals but not in those with deficiency, supports a potential interaction effect between the two nutrients [ 8 , 44 , 45 ]. Adequate levels of both, magnesium and vitamin D, may be needed for optimal muscle strength [ 46 48 ].…”
Section: Discussionmentioning
confidence: 89%
“…9 Hypertension was de ned as being told by a doctor that you have hypertension. 10 Smoking status was categorized as smoking (having smoked 100 cigarettes in a lifetime) and nonsmoking (having never smoked 100 cigarettes in a lifetime). 11 Drinking status was categorized as drinking (at least once a month) and non-drinking (less than once a month).…”
Section: De Nition Of Covariatesmentioning
confidence: 99%